1991
DOI: 10.1007/bf00317391
|View full text |Cite
|
Sign up to set email alerts
|

Thorns as induced defenses: experimental evidence

Abstract: We report evidence from controlled experiments that long straight thorns deter herbivory by browsers. Cut branches of three woody species that had their thorns removed suffered significantly greater herbivory by a tethered goat than did paired intact branches. Branches on living Acacia seyal plants that had their thorns removed suffered significantly greater herbivory by a wild population of free-ranging giraffes than did intact branches on the same plants. These differences in herbivory resulted in long term … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
174
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(179 citation statements)
references
References 24 publications
4
174
1
Order By: Relevance
“…Moreover, branches of Acacia drepanolobium Harms ex Sjöstedt (Fabaceae) within reach of goats had significantly longer thorns than higher branches on the same plants or branches at all heights on nearby plants protected from ungulate herbivory (Young, 1987), and a similar pattern has been reported qualitatively on trees eaten by giraffes (Foster & Dagg, 1972). In addition, Milewski et al (1991) and Takada et al (2003) reported that the degree of herbivory was different between prickled and non-prickled Acacia seyal Del. and Damnacanthus indicus C. F.…”
Section: Resultssupporting
confidence: 52%
“…Moreover, branches of Acacia drepanolobium Harms ex Sjöstedt (Fabaceae) within reach of goats had significantly longer thorns than higher branches on the same plants or branches at all heights on nearby plants protected from ungulate herbivory (Young, 1987), and a similar pattern has been reported qualitatively on trees eaten by giraffes (Foster & Dagg, 1972). In addition, Milewski et al (1991) and Takada et al (2003) reported that the degree of herbivory was different between prickled and non-prickled Acacia seyal Del. and Damnacanthus indicus C. F.…”
Section: Resultssupporting
confidence: 52%
“…Spinescent woody plants also have small leaves further reducing herbivore foraging efficiency since the reward received is seldom worth the time or energy needed to exploit it (Belovsky et al, 1991;Gowda, 1996). Plant spinescence increases with exposure to herbivory by large browsers as an induced defence (Milewski et al, 1991). Spines and thorns protect both leaves and axillary meristems (Gowda, 1996).…”
Section: Woody Plant Response To Herbivorymentioning
confidence: 99%
“…Spine and thorn removal experiments have been carried out to demonstrate the protective value of these structures (Wilson & Kerley, 2003b;Hanley et al, 2007). Milewski et al (1991) reported the removal of Acacia drepanolobium thorns as causing a threefold increase in mammalian browsing of new foliage. Increased rates of herbivory by bushbucks (Tragelaphus scriptus) and boergoats (Capra hircus) was also reported following the removal of thorns from spinescent shrub species in the Eastern Cape region of South Africa (Wilson & Kerley, 2003b).…”
Section: Woody Plant Response To Herbivorymentioning
confidence: 99%
See 1 more Smart Citation
“…However, primary producers may also adopt alternative defense mechanisms to cope with selective grazing, such as the production of secondary compounds (Stamp 2003;Van de Waal et al 2009), development of spines and thorns (Milewski et al 1991;Tollrian and Harvell 1999), and reinforcement of cell walls (Van Donk et al 1997;Hamm et al 2003). These defenses may enable primary producers to sustain high nutritional quality without suffering intense grazing by selective herbivores.…”
Section: A Stoichiometric Trade-offmentioning
confidence: 99%